Utilization of E-Catalog to Increase Sales of Sand and Stone Materials for Road Paving Contractors: A Case Study of PT. Pioneer - Silalahi, Flora; Ekawulandari, Sri; Surbakti, Ristina br (Journal Boas : Business, Economics, Accounting And Management, 2025)
This study aims to analyze the effectiveness of utilizing E-Catalog in increasing the sales of sand and stone material suppliers at PT. Pioneer, a road paving contractor. Alongside digital transformation in procurement processes, the use of E-Catalog has become increasingly effective in promoting efficiency and transparency. This research employs a qualitative method with a case study approach on a material supplier engaged with PT. Pioneer through the E-Catalog platform. The findings reveal that the implementation of E-Catalog significantly facilitates the material search and ordering process, reducing time and administrative costs. For suppliers, E-Catalog expands market reach and accelerates the sales cycle. The sales increase is not only due to ease of access but also from trust built through transparent and accountable procurement processes.